Strategi Guru Pendidikan Agama Islam dalam Penerapan Akhlak Mulia Siswa - Ira Safira; Khoiril Akhbar (IDRIS Darulfunun Institute, 2026)
This study aims to analyze the strategies employed by Islamic Religious Education (PAI) teachers in implementing students’ noble character (akhlak mulia), describe the implementation of affective learning in fostering students’ moral development, and identify the supporting and inhibiting factors encountered in the process at MTs Al Qodiri IV Jember. This research employed a qualitative descriptive approach. Data were collected through observation, semi-structured interviews, and documentation involving the principal, Islamic Religious Education teachers, homeroom teachers, and students. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that PAI teachers implement noble character education through exemplary behavior (uswah hasanah), religious habituation, advice (mau'idzah hasanah), and persuasive supervision. The implementation of affective learning reflects Thomas Lickona’s three dimensions of character education, namely moral knowing, moral feeling, and moral action, which are integrated into classroom instruction and religious school culture. Supporting factors include the pesantren-based environment, teachers’ commitment, and religious habituation programs, whereas inhibiting factors consist of digital media influence, peer pressure, and students’ diverse family backgrounds. This study contributes to the development of character education by presenting an adaptive strategy for integrating affective learning with Islamic values in a pesantren-based formal school, thereby enriching the discourse on Islamic character education in the digital era.